Autocratic Leadership and Authority: A Comparative Analysis of Max Weber and Michel Crozier’s Concepts - Guerroudj , Aissa; BENAISSA, Al-Azhari; Maache , Tayab (Social Sciences Journal)
This research aims to explore the concepts of autocratic and authoritarian leadership through a comparative analysis of the theories of Max Weber and Michel Crozier. Weber’s model highlights bureaucratic authority within a rational-legal framework, while Crozier emphasizes the role of organizational dynamics and the management of uncertainty in power relations. Comparing these two theorists demonstrates differing perspectives on leadership authority. Weber’s bureaucratic model enhances efficiency and predictability, whereas Crozier underscores the significance of informal dynamics and the need for adaptability and responsiveness. By integrating these two perspectives, we gain a more nuanced understanding of authoritarian leadership that acknowledges both the strengths and limitations of each approach. This comprehensive perspective is significant for contemporary leaders navigating complex organizational landscapes, where traditional hierarchies may not always apply.